Humanitarian Ecology: Balancing Human Needs and Environmental Preservation in Islamic Law - Karimullah, Suud Sarim (Faculty of Sharia and Law, Sunan Gunung Djati Islamic State University of Bandung, 2024)
Abstract: This study has a comprehensive objective of understanding the practical implications of environmental protection within the framework of Islamic law, taking into account the balance of human needs and ecological preservation. The method used is library research with literature analysis through synthesis and integration of information from various relevant sources, such as books, scientific articles, and other documents related to the research topic. The findings of the study show that environmental protection in the framework of Islamic law not only provides a solid moral and ethical foundation but also challenges the conventional paradigm in natural resource management by offering a holistic approach that integrates spiritual, social, and ecological values. Through maqasid al-sharia, environmental protection becomes an integral part of the objectives of sharia, namely preserving life (hifz al-nafs) and ecological sustainability (hifz al-biāh) by providing ethical guidance to prevent overexploitation while encouraging sustainable innovation. Thus, Islamic law not only responds to the challenges of the global environmental crisis but also offers a model of sustainability that brings together spiritual, ethical, and practical values in creating harmony between human needs and the preservation of nature, making it relevant as a strategic solution for the modern world.